Diagnosis and Management of Kaposi Sarcoma-Associated Herpesvirus Inflammatory Cytokine Syndrome in Resource-Constrained Settings: A Case Report and an Adapted Case Definition - Tapiwa Kumwenda; Daniel Z. Hodson; Kelvin Rambiki; Ethel Rambiki; Yuri Fedoriw; Christopher Tymchuk; Claudia Wallrauch; Tom Heller; Matthew S. Painschab (Tropical Medicine and Infectious Disease)
Kaposi sarcoma-associated herpes virus (KSHV), also known as human herpes virus 8 (HHV-8), is the primary etiologic cause of Kaposi sarcoma (KS) and KSHV Inflammatory Cytokine Syndrome (KICS). Patients with KICS demonstrate symptoms of systemic inflammation, high KSHV viral load, elevation of inflammatory markers, and increased mortality. Management requires rapid diagnosis, treatment of underlying HIV, direct treatment of KS, and addressing the hyperimmune response. While a case definition based on clinical presentation, imaging findings, laboratory values, KSHV viral load, and lymph-node biopsy has been proposed, some of the required investigations are frequently unavailable in resource-constrained settings. Due to these challenges, KICS likely remains underdiagnosed and undertreated in these settings. We report a case of a 19-year-old woman living with HIV, and intermittent adherence to her ART, who presented with hypotension and acute hypoxemic respiratory failure. She was found to have high KSHV and HIV viral loads, low CD4 count, anemia, thrombocytopenia, hypoalbuminemia, and elevated inflammatory markers. On bedside ultrasound, she was found to have bilateral pleural effusions, ascites, an enlarged spleen, and hyperechoic splenic lesions. The diagnosis of KICS was made based on this constellation of findings. Weighing the risk and benefits of steroid administration in KS patients, the patient was successfully treated by the continuation of ART and the initiation of paclitaxel chemotherapy and steroids. We propose an adapted case definition relevant to the resource-constrained context. Due to the dual burden of KSHV and HIV in sub-Saharan Africa, additional cases of KICS are likely, and this syndrome will contribute to the burden of early mortality in newly diagnosed HIV patients. Addressing the diagnostic and therapeutic challenges of KICS must be a part of the overall management of the HIV pandemic.